Lean transformation sustainability models: a critical review / Azim Azuan Osman, Rusalbiah Che Mamat and Mazita Mat Ali - Osman, Azim Azuan; Che Mamat, Rusalbiah; Mat Ali, Mazita (Faculty of Business and Management UiTM Shah Alam, 2020)
Transformation from conventional production system to lean production system has helped many manufacturing companies to reduce cost and ultimately improve their business performance. Unfortunately, there were also many reported cases where manufacturers failed to sustain the transformation until they achieve the ultimate result. Therefore, this article aimed to review existing Lean Transformation Sustainability (LTS) models that might help scholars and practitioners gain better insights on how to sustain lean transformation. This article compiled 37 LTS models through assistance of online bibliographic databases. The review study found that many researchers have proposed original models which involved high participation of practitioners and to some extent consultants in the development of LTS models. It was also found that a huge number of inconsistent elements were used to propose the LTS models. The study findings provided direction towards future research opportunities such as the development of LTS assessment model that encompassed standard set of elements for generalisation.